Answer gets brainliest
![Answer gets brainliest class=](https://us-static.z-dn.net/files/dfa/f37fb740f0f7aa37a82702376cd4630e.png)
Answer:
(- 3.5, - 5.5 )
Step-by-step explanation:
y = x - 2 → (1)
y = 3x + 5 → (2)
substitute y = 3x + 5 into (1)
3x + 5 = x - 2 ( subtract x from both sides )
2x + 5 = - 2 ( subtract 5 from both sides )
2x = - 7 ( divide both sides by 2 )
x = - 3.5
substitute x = - 3.5 into either of the 2 equations
substituting into (1)
y = - 3.5 - 2 = - 5.5 )
solution is (- 3.5, - 5.5 )